Sound and musical instruments in the Holocene archaeological record of South Africa - Kumbani, Joshua (My University, 2020)
This thesis provides the first evidence of music-related and sound producing artefacts from the last 10000 years in southern Africa. An inventory of artefacts from southern Africa, including an ivory trumpet, whistles, iron gongs or bells, thumb piano keys or lamellophone keys and rock gongs, show that such artefacts are very rare. This is due to poor preservation of instruments that are frequently made of organic material that rarely survive in the archaeological record. Actualistic studies and microscopic analysis have indicated that two Holocene dual holed bone implements, from Klasies River main site and Matjes River, could have been used as spinning disks, artefacts that produce a whirring sound when spun in front of the body. This approach further identified the first archaeological bullroarer from southern Africa, a bone implement previously interpreted as a pendant from Wilton layers at Matjes River. Sounds recorded from replicas of the bullroarer indicate sound qualities and frequencies similar to other bullroarers from the ethnographic and archaeological record. Bone tubes or pipes that could have been used as flutes or whistles also come from these layers from Matjes River. Rock art images of musical bow players from the Maloti Drakensberg Mountains in KwaZulu-Natal and in the Eastern Cape Province of South Africa are discussed and compared to ethnographic and contemporary musical bow playing. Depictions of flute playing from the Klein Karoo as well as the Cederberg are presented and linked to possible similar activities from the South African ethnographic record. It is clear that there is great potential to further music archaeological research in South Africa and the southern African region. This multidisciplinary research into the archaeological evidence for sound and musical expressions from southern Africa adds new knowledge and data to enrich to enrich our understanding of Holocene social practices
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020
Keywords: Music archaeology; Archaeology; Musical instruments